Stem cell-derived exosomes for dentin-pulp complex regeneration: a mini-review - Dina A. Hammouda; Alaa M Mansour; Mahmoud A. Saeed; Ahmed R. Zaher; Mohammed E. Grawish (Restorative Dentistry & Endodontics)
This mini-review was conducted to present an overview of the use of exosomes in regenerating the dentin-pulp complex (DPC). The PubMed and Scopus databases were searched for relevant articles published between January 1, 2013 and January 1, 2023. The findings of basic in vitro studies indicated that exosomes enhance the proliferation and migration of mesenchymal cells, as human dental pulp stem cells, via mitogen-activated protein kinases and Wingless-Int signaling pathways. In addition, they possess proangiogenic potential and contribute to neovascularization and capillary tube formation by promoting endothelial cell proliferation and migration of human umbilical vein endothelial cells. Likewise, they regulate the migration and differentiation of Schwann cells, facilitate the conversion of M1 pro-inflammatory macrophages to M2 anti-inflammatory phenotypes, and mediate immune suppression as they promote regulatory T cell conversion. Basic in vivo studies have indicated that exosomes triggered the regeneration of dentin-pulp–like tissue, and exosomes isolated under odontogenic circumstances are particularly strong inducers of tissue regeneration and stem cell differentiation. Exosomes are a promising regenerative tool for DPC in cases of small pulp exposure or for whole-pulp tissue regeneration.